SOD1 dimerization monitoring using a novel split NanoLuc, NanoBit. (29th September 2016) - Oh‐hashi, Kentaro; Hirata, Yoko; Kiuchi, Kazutoshi
Abstract : In the present study, we applied a highly sensitive NanoLuc‐based technology to understand the status of superoxide dismutase 1 (SOD1) within mammalian cells. Two fragments of NanoLuc (NanoBit), large N‐terminal and small C‐terminal regions, were fused with wild‐type (wt) and mutant human SOD1 (hSOD1) genes and transfected into cells. Luciferase activity through NanoBit assembly was only detected in NanoBit‐tagged wtSOD1‐expressing cells. Furthermore, the developed NanoLuc system was used to investigate the role of protein‐protein interactions in the pathogenesis of amyotrophic lateral sclerosis (ALS). In addition to SOD1, we also applied this NanoBit system for detecting the dimerization of wild‐type, M337V‐mutated human TAR‐binding protein 43 kDa (hTDP43) and its cleaved C‐terminal fragment (TDP25M337V ) as well as their interactions with SOD1. Luciferase activities of NanoBit‐tagged mutant SOD1, TDP43, or TDP25 were negligible. Finally, we found that a zinc chelator partially reduced the luciferase activity of NanoBit‐wtSOD1. Collectively, these results show that the present assay is sensitive and convenient to appreciate ALS and to develop useful agents for the modulation of SOD1 conformation.